The money pitch : baseball free agency and salary arbitration - Abrams, Roger I., 1945- (Temple University Press, 2000)
Professional baseball players have always been well paid. In 1869, Harry Wright paid his Cincinnati Red Stockings about seven times what an average working-man earned. Today, on average, players earn more than fifty times the average worker's salary. In fact, on December 12, 1998, pitcher Kevin Brown agreed to a seven-year, $105,000,000 contract with the Los Angeles Dodgers, the first nine-figure contract in baseball history. Brown will be earning over $400,000 per game; more than 17,000 fans have to show up at Dodger Stadium every night just to pay his salary. Why are baseball players paid so much money? In this insightful book, legal scholar and salary arbitrator Roger Abrams tells the story of how a few thousand very talented young men obtain their extraordinary riches. Juggling personal experience and business economics, game theory and baseball history, he explains how agents negotiate compensation, how salary arbitration works, and how the free agency "auction" operates. In addition, he looks at the context in which these systems operate: the players' collective bargaining agreement, the distribution of quality players among the clubs, even the costs of other forms of entertainment with which baseball competes. Throughout, Dean Abrams illustrates his explanations with stories and quotations -- even an occasional statistic, though following the dictum of star pitcher, club owner, and sporting goods tycoon Albert Spalding, he has kept the book as free of these as possible. He explains supply and demand by the cost of a bar of soap for Christy Mathewson's shower. He illustrates salary negotiation with an imaginary case based on Roy Hobbs, star of The Natural. He leads the readerthrough the breath-taking successes of agent Scott Boras to explain the intricacies of free agent negotiating. Although studies have shown that increases in admissions prices precede rather than follow the rise in player salaries, fans are understandably bemused by skyrocketing salaries. Dean Abrams does not shy away from the question of whether it is "fair" for an athlete to earn more than $10,000,000 a year. He looks at issues of player (and team) loyalty and player attitudes, both today and historically, and at what increased salaries have meant for the national pastime, financially and in the eyes of its fans. The Money Pitch concludes that "the money pitch is a story of good fortune, good timing, and great leadership, all resulting from playing a child's game -- a story that is uniquely American."